2006
DOI: 10.1021/es0609708
|View full text |Cite
|
Sign up to set email alerts
|

Stable Colloidal Dispersions of C60 Fullerenes in Water: Evidence for Genotoxicity

Abstract: Stable aqueous suspensions of colloidal C60 fullerenes free of toxic organic solvents were prepared by two methods: ethanol to water solvent exchange (EthOH/nC60 suspensions) and extended mixing in water (aqu/nC60 suspensions). The extended mixing method resulted in the formation of larger (dp approximately 178 nm) and less negatively charged (zeta approximately -13.5 mV) nC60 colloids than nC60 prepared by ethanol to water solvent exchange (dp approximately 122 nm, zeta approximately -31.6 mV). Genotoxicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
203
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 44 publications
8
203
1
6
Order By: Relevance
“…In vitro studies on silver nanoparticles' toxicity have suggested that interference with DNA replication, fidelity, apoptosis, oxidative stress, cytotoxicity, chromosome instability, intracellular calcium transients, JNK activation and cell cycle arrest in mammalian cells [121-125, 140, 141]. Fullerenes are responsible for DNA damage and oxidative stress in mammalian cells lines [142][143][144]. In a study on FE1-Muta™ mouse lung, epithelial cells were investigated to observe the effects of C 60 fullerenes and SW-CNTs for cytotoxicity, genotoxicity and ROS production [142].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…In vitro studies on silver nanoparticles' toxicity have suggested that interference with DNA replication, fidelity, apoptosis, oxidative stress, cytotoxicity, chromosome instability, intracellular calcium transients, JNK activation and cell cycle arrest in mammalian cells [121-125, 140, 141]. Fullerenes are responsible for DNA damage and oxidative stress in mammalian cells lines [142][143][144]. In a study on FE1-Muta™ mouse lung, epithelial cells were investigated to observe the effects of C 60 fullerenes and SW-CNTs for cytotoxicity, genotoxicity and ROS production [142].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Many authors have reported on the photophysical properties of molecular solutions of C 60 . [12][13][14][15][16][17][18][19][20] Likewise, many authors have studied the photophysical and structural properties of solid films of C 60 . [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Under certain conditions, C 60 forms stable colloidal assemblies in solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Likewise, many authors have studied the photophysical and structural properties of solid films of C 60 . [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Under certain conditions, C 60 forms stable colloidal assemblies in solvents. [35][36][37][38][39][40][41][42][43][44] Colloidal suspensions of C 60 particles can also be formed in binary solvent mixtures, in which one is a good solvent and the other is a poor solvent for C 60 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using atomistic molecular dynamics simulations, Zhao et al [19] demonstrated that C 60 could strongly bind to nucleotides, suggesting that C 60 molecules have a potentially negative impact on the structure, stability, and biological functions of DNA molecules. Recently, the possible genotoxicity of C 60 was demonstrated by using single-cell gel electrophoresis assay [20].…”
Section: Introductionmentioning
confidence: 99%